A Comprehensive Framework for Emergency Message Dissemination in Urban VANET Scenarios: A Comparative Analysis of Clustering-Based Routing Protocols - Ravneet Kaur; Chaitanya Singla; Harpal Singh; Rajat Bhardwaj; Preeti Sharma; Ambika Aggarwal; Deema Mohammed Alsekait; Diaa Salama Abd Elminaam (IEEE Access)
The future of smart cities depends on Vehicular Ad hoc Networks that offer services from safety applications to infotainment. However, significant challenges in urban scenarios include connectivity issues, routing, obstacles, and path loss. This paper proposes a comprehensive framework for emergency message dissemination in urban Vehicular Adhoc Network scenarios, focusing on a comparative analysis of clustering-based routing protocols. The RSU Assisted Multi-Hop Weighted Mobility (RA-MHWM) clustering algorithm is proposed as a promising solution, consisting of an RSU Assisted Hybrid Multi-Hop Weighted Mobility for Cluster Head selection algorithm and a Sub-Cluster Head algorithm. The routing is implemented using Cross Layer Weighted Position Based Routing Protocol (CLWPR), Ad hoc On-Demand Distance Vector, and Connected Junction Based Routing (CJBR) protocols, which are compared with each other. A forwarder gateway node selection mechanism is proposed to maximize information coverage. The analysis evaluates that RA-MHWM with CLWPR and CJBR possess significantly higher average throughput, increased Packet Delivery Ratio, and decreased average end-to-end delivery compared to RA-MHWM with AODV and other protocols. Notably, RA-MHWM with CJBR outperforms in terms of information coverage by 85% to deliver emergency messages compared to other protocols for intra-cluster communication.